Perchlorate‐induced combustion of organic matter with variable molecular weights: Implications for Mars missions. Issue 21 (11th November 2014) - Sephton, Mark A.; Lewis, James M. T.; Watson, Jonathan S.; Montgomery, Wren; Garnier, Carole
Abstract Instruments on the Viking landers and Curiosity rover analyzed samples of Mars and detected carbon dioxide and organic compounds of uncertain origin. Mineral‐assisted reactions are leading to uncertainty, particularly those involving perchlorate minerals which thermally decompose to produce chlorine and oxygen which can then react with organic matter to generate organochlorine compounds and carbon dioxide. Although generally considered a problem for interpretation, the release profiles of generated gases can indicate the type of organic matter present. We have performed a set of experiments with perchlorate and organic matter of variable molecular weights. Results indicate that organic susceptibility to thermal degradation and mineral‐assisted reactions is related to molecular weight. Low molecular weight organic matter reacts at lower temperatures than its high molecular weight counterparts. The natural occurrence and association of organic matter with differing molecular weights helps to discriminate between contamination (usually low molecular weight organic matter only) and indigenous carbon (commonly low and high molecular weight organic matter together). Our results can be used to provide insights into data returning from Mars.